1994
DOI: 10.1002/ptr.2650080407
|View full text |Cite
|
Sign up to set email alerts
|

Antihepatotoxic and immunostimulant properties of iridoid glycosides of Scrophularia koelzii

Abstract: The alcoholic extract of the aerial parts of Scrophularia koelzii (100 mg/kg p.0. X 7 days) significantly protected the rat liver against thioacetamide induced toxicity. On its further fractionation, activity was localized in the chloroform fraction from which four iridoid glycosides, namely scropolioside-A, koelzioside, harpagoside and 6-O-(3"-O-p-methoxy-cinnamoyl)-u-L-rhamnopyranosyl catalpol were isolated. Among these, scropolioside-A showed maximum hepatoprotective activity. Immunostimulant response was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 11 publications
0
22
0
2
Order By: Relevance
“…These results were supported by histological studies. Iridoid glycosides from many plants are known for their antihepatotoxic and antioxidant effect (Garg et al, 1994), respectively. They are considered to be the active principles of many medicinal plants (Ghisalberti, 1998;Dinda et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These results were supported by histological studies. Iridoid glycosides from many plants are known for their antihepatotoxic and antioxidant effect (Garg et al, 1994), respectively. They are considered to be the active principles of many medicinal plants (Ghisalberti, 1998;Dinda et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While both compounds 232 and 233 showed a negative dose-dependent response, stimulating HDF growth at lower concentration (highest at 0.78 mg/ml). Scopolioside A was also found to possess immunostimulant property 119) and compound 232 anti-inflammatory activity. 120) Hence the use of the extract of S. nodosa containing these compounds for wound healing treatment as folk medicine is justified.…”
Section: )mentioning
confidence: 99%
“…The iridoids are groups of natural molecules with a monoterpene cyclic ring, found in a wide variety of plants (Tietze, 1983). The previous phytochemical studies reported that iridoid glucoside possesses a number of activities such as antitumoral, hypotensive, sedative and hepatoprotective activities (Garg et al, 1994;Ghisalberti, 1998). The in vitro effects of SPC have been reported earlier while the limited in vivo effects have been studied.…”
Section: Introductionmentioning
confidence: 97%